Peranan Ibu Bapa Dalam Melahirkan Huffaz Al-Quran Yang Cemerlang Di Era Kecerdasan Buatan (Ai) - Hayati Hussin; Abdul Rahim Ahmad; Muhammad Hafiz Saleh; Norullisza Khosim; Mardhiah Yahaya; Noor Hafizah Mohd Haridi (Yayasan Dakwah Islamiah Malaysia, 2026)
Non-Indexed Publication